Short Communication: In Vitro Efficacy Testing of Praziquantel, Ivermectin, and Oxfendazole against Taenia Solium Cysts - S. Cederberg; C. S. Sikasunge; Å. Andersson; M. V. Johansen (Journal of Parasitology Research)
Oxfendazole is recommended as the drug of choice for treating porcine cysticercosis. The drug does not kill brain cysts and is not registered for use in pigs. Latest its safety in the recommended dose has been questioned. The aim of this study was to investigate two alternative anthelminthics. The efficacy of praziquantel and ivermectin was compared to oxfendazole In Vitro on Taenia solium. Cysts of T. solium were isolated from infected pork and incubated in culture media together with the drugs. The degree of evagination was used as effect measurement and determined after 6 hours. Praziquantel had a half maximal effective concentration (EC50) of value 0.006 ± 0.001 μg/mL. Ivermectin did not show any impact on the evagination in concentrations from 0.001 to 30 μg/mL and neither did oxfendazole in concentrations from 0.001 to 50 μg/mL.